Relationships Between Self-Rated Health at Three Time Points: Past, Present, Future - Hinz, Andreas; Friedrich, Michael; Luck, Tobias; Riedel-Heller, Steffi G.; Mehnert-Theuerkauf, Anja; Petrowski, Katja (Frontiers in Psychology, 2022)
Background: Multiple studies have shown that people who have experienced a serious health problem such as an injury tend to overrate the quality of health they had before that event. The main objective of this study was to test whether the phenomenon of respondents overrating their past health can also be observed in people from the general population. A second aim was to test whether habitual optimism is indeed focused on events in the future. Method: A representatively selected community sample from Leipzig, Germany (n = 2282, age range: 40 – 75 years) was examined. Respondents were asked to assess their current health, their past health (5 years before), and their expected future health (in 5 years) on a 0-100 scale. In addition, the study participants completed several questionnaires on specific aspects of physical and mental health. Results: Respondents of all age groups assessed their health as having been better in the past than it was at present. Moreover, they also assessed their earlier state of health more positively than people five years younger did their current state. Habitual optimism was associated with respondents having more positive expectations of how healthy they will be in five years time (r = 0.37), but the correlation with their assessments of their current health was nearly as high (r = 0.36). Conclusions: Highly positive scores of retrospectively assessed health among people who have experienced a health problem cannot totally be accounted for by a response to that health problem.